Politicians on celebrity talk shows. (December 2017) - Loeb, Laura
Abstract: Politicians frequently appear on entertainment talk shows like The Tonight Show and The View, particularly during election campaigns. Previous research shows these appearances can inform and sway voters, but the practices of these interviews are still not fully understood. This study builds on previous work on talk show and news interview norms to measure the normative organization of interviewing in this environment. The findings suggest that these interviews represent a blending of news and talk show norms. This results in a distinctive type of interview and gives candidates unique opportunities and challenges. This study provides insight into an understudied aspect of the current media landscape, and into the pressures that shape today's election campaigns.